Pembuatan Media Pembelajaran Bahasa Inggris “EnglishEasy” untuk SMK Menggunakan Kodular Berbasis Android - Purbasari, Dita Anggi; Harjono, Harjono -; Melianingsih, Nuning; Wimuryanti, Esty Dyah (Jurnal Ilmiah SINUS, 2025)
The purpose of this research is to design android application as English learning media for vocational high school by using Kodular. Based on the pre-observation, the researchers found out that the students had limit resources to learn English since they only have one source from the book, the students demanded to have learning sources that can be used anytime and everywhere. Besides, it is expected that it is able to help the students to learn more about TOEIC. The researchers decided to design android application as English learning media by using Kodular. It can be applied to students’ smartphone and will be able to be accessed anytime and everywhere. Research & Development is used as research method. There are several steps to be conducted, they are: 1) analyze students’ need; 2) collecting data; 3) designing prototype; 4) trying out product; 5) final product. The result of this research is English android application based on Kodular, namely EnglishEasy.